FlexiXML : a portable user interface rendering engine for UsiXML - Campos, J. Creissac (2011)
A considerable amount of effort in software development is dedicated to the user interaction layer.Given the complexity inherent to the development of this layer, it is important to be able to analyse the concepts and ideas being used in the development of a given user interface. This analysis should be performed as early as possible. Model- based user interface development provides a solution to this problem by providing developers with tools that enable both modeling, and reasoning about, user interfaces at different levels of abstraction. Of particular interest here, is the possibility of animating the models to generate actual user interfaces. This paper describes FlexiXML, a tool that performs the rendering and animation of user interfaces described in the UsiXML modeling language.